An epigenome-wide association study of metabolic syndrome and its components - Marja-Liisa Nuotio (Nature Portfolio, 2020)
Abstract The role of metabolic syndrome (MetS) as a preceding metabolic state for type 2 diabetes and cardiovascular disease is widely recognised. To accumulate knowledge of the pathological mechanisms behind the condition at the methylation level, we conducted an epigenome-wide association study (EWAS) of MetS and its components, testing 1187 individuals of European ancestry for approximately 470 000 methylation sites throughout the genome. Methylation site cg19693031 in gene TXNIP —previously associated with type 2 diabetes, glucose and lipid metabolism, associated with fasting glucose level (P = 1.80 × 10−8). Cg06500161 in gene ABCG1 associated both with serum triglycerides (P = 5.36 × 10−9) and waist circumference (P = 5.21 × 10−9). The previously identified type 2 diabetes–associated locus cg08309687 in chromosome 21 associated with waist circumference for the first time (P = 2.24 × 10−7). Furthermore, a novel HDL association with cg17901584 in chromosome 1 was identified (P = 7.81 × 10−8). Our study supports previous genetic studies of MetS, finding that lipid metabolism plays a key role in pathology of the syndrome. We provide evidence regarding a close interplay with glucose metabolism. Finally, we suggest that in attempts to identify methylation loci linking separate MetS components, cg19693031 appears to represent a strong candidate.